IMPROVING ORGANIZATIONAL AND ECONOMIC MECHANISMS FOR SUPPORTING WOMEN'S ENTREPRENEURSHIP IN THE SERVICE SECTOR (The Conference Hub, 2025)
This article focuses on the enormous potential of women's entrepreneurship in the service sector. Women's entrepreneurship demonstrates a high level of initiative and willingness to take responsibility, but the issues of facing a lack of financial resources, information support, and practical knowledge are studied and suggestions and recommendations are made.